CSIG-19. THE PI3K/AKT/MTOR SIGNALING CASCADE MAY CONTRIBUTE TO SEX DIFFERENCES IN GLIOBLASTOMA. (14th November 2022) - Sponagel, Jasmin; Johnston, Hannah; Gass, Hannah; Nunez, Elena; Ippolito, Joseph; Rubin, Joshua
Abstract: Glioblastoma (GBM) is the most common and aggressive primary brain tumor in adults. It is more prevalent in males and female patients exhibit a survival advantage. Understanding the molecular mechanisms that underlie those sex differences could support novel treatment strategies. The PI3K/Akt/mTOR signaling cascade plays a crucial role in GBM development and progression as it is involved in the regulation of cellular growth, survival, nutrient sensing, and metabolic activity. To investigate whether the PI3K/Akt/mTOR signaling cascade may differ in male and female GBM patients, we first assessed survival data of male and female GBM patients using the TCGA RPPA phosphoproteome data set and found that changes in protein phosphorylation of components of the PI3K/Akt/mTOR pathway, including mTOR phosphorylation, worsen the outcome of male but not female GBM patients in a dose-dependent fashion. This was supported by in vitro experiments of murine transformed astrocytes where pathway stimulation via treatment with insulin, IGF-1, or EGF significantly increased pathway activity in male but not female cells. Furthermore, pathway inhibition via serum deprivation resulted in a significant decrease in pathway activity in male but not female cells, indicating that male transformed astrocytes exhibit higher sensitivity to inhibitory conditions (serum deprivation) and stimulatory conditions (insulin, IGF-1, or EGF treatment). Together, these data suggest that (i) the PI3K/Akt/mTOR pathway activity may affect male and female GBM outcome differently, and (ii) there are sex differences in the regulation of the PI3K/Akt/mTOR signaling cascade in GBM which may contribute to the sex disparity in GBM. Our data add to the growing body of literature regarding the presence of sex differences in PI3K/Akt/mTOR signaling in health and disease and provide important insight for the development of translatable approaches to treatment for male and female GBM patients.